PENGARUH SISTEM PENGENDALIAN INTERN PEMERINTAH DAN KOMITMEN ORGANISASI TERHADAP KINERJA INSTANSI PEMERINTAH DENGAN GOOD GOVERNANCE SEBAGAI VARIABEL INTERVENING (Studi Empiris OPD Provinsi Sumatra Barat) - Arries Martin Riafan; Desmiyawati Desmiyawati; Nur Azlina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aimed to analyze the direct and indirect effects of governmentinternal control systems, organizational commitment to the performance ofgovernment agencies through good governance as an intervening variable. Thisresearch was conducted in 28 Regional Apparatus Organizations in West SumatraProvince with 99 respondents. The data is analyzed using PLS (Partial LeastSquare) analysis techniques. While the sampling method uses a saturated samplemethod. The results showed that the internal control system, organizationalcommitment has a direct influence on the performance of government agenciesthrough good governance, for the indirect influence of good governance mediatesthe relationship between government internal control systems on the performanceof government agencies, while organizational commitment to good governanceperformance is unable to mediate.Keywords : Performance of government agencies, government internal controlsystems, organizational commitment, good governance.